2004
DOI: 10.1557/proc-810-c4.12
|View full text |Cite
|
Sign up to set email alerts
|

Strain Relaxation of Ion-implanted Strained Silicon on Relaxed SiGe

Abstract: The relaxation processes of strained silicon films on silicon-rich relaxed SiGe alloys have been studied. Experimental structures were generated via Molecular Beam Epitaxial (MBE) growth techniques and contain a strained silicon capping layer of approximately 50 nm. The relaxed SiGe alloy compositions range from 0 to 30 atomic% germanium. Samples received two distinct types of silicon implants. A 12 keV Si + implant at a dose of 1x10 15 atoms/cm 2 was used to generate an amorphous layer strictly confined withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, the volumetric strain is strongly dependent on the fraction ratio between Si and Ge. For instance, while x = 0.1 in Si/Si 1-x Ge x would result in a small volumetric strain of 2.28%, x = 0.3 could give a volumetric strain as high as 7.2% (i.e., [25]). We also point out that the simple assumption of volumetric strain is closely associated with the quantum wire and quantum dot growth modes in cubic semiconductors (i.e., [1]).…”
Section: Discussionmentioning
confidence: 99%
“…However, the volumetric strain is strongly dependent on the fraction ratio between Si and Ge. For instance, while x = 0.1 in Si/Si 1-x Ge x would result in a small volumetric strain of 2.28%, x = 0.3 could give a volumetric strain as high as 7.2% (i.e., [25]). We also point out that the simple assumption of volumetric strain is closely associated with the quantum wire and quantum dot growth modes in cubic semiconductors (i.e., [1]).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also employed rocking curves to study the strain relaxation observed in the strained silicon capping layer using pseudomorphic Si/Si 1Àx Ge x structures [11,12]. However, further investigation determined space maps to be a preferable technique for the measurement of annealed samples.…”
Section: Experimental Designmentioning
confidence: 99%
“…2,3 Ion implantation creates point defects, which act as nucleation sites for relaxation induced dislocation or aid in the inter-diffusion of Boron and Ge, resulting in accelerated strain relaxation. [4][5][6] This leads to a lower hole mobility and higher junction leakage therefore degrading device performance.…”
mentioning
confidence: 99%